Spliced X-box Binding Protein 1 Stimulates Adaptive Growth Through Activation of mTOR. Issue 7 (13th August 2019) - Wang, Xiaoding; Deng, Yingfeng; Zhang, Guangyu; Li, Chao; Ding, Guanqiao; May, Herman I.; Tran, Diem H.; Luo, Xiang; Jiang, Ding-Sheng; Li, Dan L.; Wei, Xiang; Xu, Lin; et al.
Abstract : Background: The unfolded protein response plays versatile roles in physiology and pathophysiology. Its connection to cell growth, however, remains elusive. Here, we sought to define the role of unfolded protein response in the regulation of cardiomyocyte growth in the heart. Methods: We used both gain- and loss-of-function approaches to genetically manipulate XBP1s (spliced X-box binding protein 1), the most conserved signaling branch of the unfolded protein response, in the heart. In addition, primary cardiomyocyte culture was used to address the role of XBP1s in cell growth in a cell-autonomous manner. Results: We found that XBP1s expression is reduced in both human and rodent cardiac tissues under heart failure. Furthermore, deficiency of XBP1s leads to decompensation and exacerbation of heart failure progression under pressure overload. On the other hand, cardiac-restricted overexpression of XBP1s prevents the development of cardiac dysfunction. Mechanistically, we found that XBP1s stimulates adaptive cardiac growth through activation of the mechanistic target of rapamycin signaling, which is mediated via FKBP11 (FK506-binding protein 11), a novel transcriptional target of XBP1s. Moreover, silencing of FKBP11 significantly diminishes XBP1s-induced mechanistic target of rapamycin activation and adaptive cell growth. Conclusions: Our results reveal a critical role of the XBP1s–FKBP11–mechanistic target of rapamycin axis in coupling of the unfolded protein response and cardiac cell growth regulation. Abstract : Supplemental Digital Content is available in the text.